2019
DOI: 10.15199/48.2019.04.17
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dynamic stability of the belt conveyor adaptive drive

Abstract: Dynamic stability of the adaptive hydraulic drive of the belt conveyor is studied with the help of an improved mathematical model constructed taking into account the physical processes that occur during the mechanical system of the conveyor under load changes. The parameters of the adaptive drive, which provide stable operation of the mechanical system in conditions of its overload, are determined.Streszczenie. Dynamiczna stabilność adaptacyjnego napędu hydraulicznego przenośnika taśmowego jest badana za pomoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Theoretical studies of the dynamic processes of the SSS of the conveyor for the action of variable loads were carried out by methods of physical and mathematical modeling. The solution of the improved mathematical model was performed using the software package MATLAB Simulink, which was used in previous studies of the hydraulic system [2,12,13]. 0.1% modeling accuracy and the 2nd order Rosenbrock research method have proven to be a qualitative way to calculate such systems.…”
Section: Research and Modeling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical studies of the dynamic processes of the SSS of the conveyor for the action of variable loads were carried out by methods of physical and mathematical modeling. The solution of the improved mathematical model was performed using the software package MATLAB Simulink, which was used in previous studies of the hydraulic system [2,12,13]. 0.1% modeling accuracy and the 2nd order Rosenbrock research method have proven to be a qualitative way to calculate such systems.…”
Section: Research and Modeling Methodsmentioning
confidence: 99%
“…1). D'Alembert's principle is applied to the forces acting on the moving elements of the mechanical system and the balance of the working fluid flow [13]. In the differential equations of change of the moment of forces of useful resistance, action of forces of viscous friction on rotating elements of hydraulic motors, change of directions of movement of working liquid in the course of work of CD, energy dissipation during movement of moving elements of system are considered.…”
Section: Fig 1 Calculation Scheme Of the Built-in Hydraulic Drive Wit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the conditions of the hydraulically driven systems operation showed that the inertial loading, torsional shiffness, volume of the pressure pipe and the character of the load change influence the transient processes of the hydraulically driven installation [20].…”
Section: Fig 10 Transient Process In the Adaptive Hydraulic Drive Omentioning
confidence: 99%